European energy security: Challenges and green opportunities - Almas Heshmati; Shahrouz Abolhosseini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This research reviews relevant literature on the current state and effectiveness of developing renewable energy on energy security in general, and on energy security in the European Union in particular. The paper elaborates on primary energy import sources, possible alternatives, and how energy security is affected by the sources of supply. It also gives an analysis of the effects of the Ukrainian crisis, the isolation of Iran on diversification sources, and on European energy security. It examines European Union's energy policy, analyses the best motivation for a new energy policy direction within Europe, and suggests alternative solutions for enhanced energy supply security. The aim is to suggest suitable solutions for energy security in Europe through energy supply diversification. Supply diversification includes alternative energy corridors for reducing dependency on Russia as a supplier and enhancing the power generated by renewable energy sources under the European Union 2020 strategy.
Keywords: 330; energy security; green energy; renewable energy; Ukraine crisis; Iran sanctions